2021
DOI: 10.3390/ijms22020562
|View full text |Cite
|
Sign up to set email alerts
|

Computational Identification of Master Regulators Influencing Trypanotolerance in Cattle

Abstract: African Animal Trypanosomiasis (AAT) is transmitted by the tsetse fly which carries pathogenic trypanosomes in its saliva, thus causing debilitating infection to livestock health. As the disease advances, a multistage progression process is observed based on the progressive clinical signs displayed in the host’s body. Investigation of genes expressed with regular monotonic patterns (known as Monotonically Expressed Genes (MEGs)) and of their master regulators can provide important clue for the understanding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 161 publications
2
5
0
Order By: Relevance
“…Similar to previous studies [ 40 , 47 , 48 , 49 , 50 , 51 ], we detected upstream regulators that regulate a set of DEGs through concerted coordination of TFs and intermediary modulators. More precisely, these so-called master regulators (key nodes) are found on top of the regulatory hierarchy of complex regulatory networks, leading to the finely tuned gene expression of a gene set.…”
Section: Methodssupporting
confidence: 86%
“…Similar to previous studies [ 40 , 47 , 48 , 49 , 50 , 51 ], we detected upstream regulators that regulate a set of DEGs through concerted coordination of TFs and intermediary modulators. More precisely, these so-called master regulators (key nodes) are found on top of the regulatory hierarchy of complex regulatory networks, leading to the finely tuned gene expression of a gene set.…”
Section: Methodssupporting
confidence: 86%
“…In this section, we illustrate an overview of the analyses to highlight the difference between our previous studies [37,38] and the current study. Simultaneously this overview shows how this present study complements our previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…Particularly, by considering the AAT disease development as a multi-stage progression process, we investigated Monotonically Expressed Genes (MEGs) to capture the complete progression process of the disease. As a result of our previous studies [37,38], we reported several transcription factors (TFs), their co-operations and master regulators governing the upstream molecular mechanism during the infection. Despite the rich literature on this disease, there is still a need for further investigation of genetic mechanisms of the regulatory processes addressing the complex interplay between regulatory SNPs, their corresponding gene expression and the downstream effectors in association with the AAT disease.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations